2022
DOI: 10.3389/fgene.2022.870640
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Investigating Functional Dynamics of Chromatin

Abstract: Dynamics spanning the picosecond-minute time domain and the atomic-subcellular spatial window have been observed for chromatin in vitro and in vivo. The condensed organization of chromatin in eukaryotic cells prevents regulatory factors from accessing genomic DNA, which requires dynamic stabilization and destabilization of structure to initiate downstream DNA activities. Those processes are achieved through altering conformational and dynamic properties of nucleosomes and nucleosome–protein complexes, of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 120 publications
0
5
0
Order By: Relevance
“…The findings of combinations of proteins associated with Propolis and COVID-19 were then filtered using the parameter P-value <0.05 to quantify statistical differences and target potential [42]- [44]. The Gene Ontology of Biological Process and KEGG target data were shown using the Bioinformatics website platform (http://www.bioinformatics.com.cn) [45]- [48] and GraphPad Prism 9.0.0.…”
Section: Enrichment Analysismentioning
confidence: 99%
“…The findings of combinations of proteins associated with Propolis and COVID-19 were then filtered using the parameter P-value <0.05 to quantify statistical differences and target potential [42]- [44]. The Gene Ontology of Biological Process and KEGG target data were shown using the Bioinformatics website platform (http://www.bioinformatics.com.cn) [45]- [48] and GraphPad Prism 9.0.0.…”
Section: Enrichment Analysismentioning
confidence: 99%
“…The organization of chromatin in space is one of the key determinants of the functional state of genes and genomes. Several decades of research has revealed that open or accessible chromatin generally promotes DNA transactions while densely folded chromatin significantly limits enzyme mobility and access to DNA substrates ( 1 , 2 ). Eukaryotic organisms take advantage of the ability to finely tune the organization of chromatin in space to enhance the efficiency, fidelity, and regulation of vital cellular processes such as gene transcription, DNA repair and genome segregation.…”
Section: Introduction: Chromatin Organization and Smc-family Enzymesmentioning
confidence: 99%
“…Changes in chromatin state is a complex affair typically requiring multi-step processes that involve nucleosomes, post-translational modifications (PTMs) of histones, as well as chromatin remodeling enzymes ( 1 , 2 ). This paradigm represents the prevalent view of how chromatin organization is regulated in interphase cells.…”
Section: Introduction: Chromatin Organization and Smc-family Enzymesmentioning
confidence: 99%
“…While significant progress has been made in atomic-resolution structure determination for nucleosomes, nucleosome arrays and their complexes with chromatin binding proteins by X-ray crystallography and, more recently, cryo-electron microscopy ( Zhou et al, 2019 ; Bai and Zhou, 2021 ; Takizawa and Kurumizaka, 2022 ), as well as characterization of conformational dynamics of histone tail and core domains in mononucleosomes by solution-state nuclear magnetic resonance (NMR) spectroscopy ( Musselman and Kutateladze, 2022 ), studies of histone protein structure, conformational dynamics and interactions in condensed nucleosomes and nucleosome arrays representative of chromatin at physiological concentrations come with considerable challenges that can uniquely be addressed by using magic angle spinning solid-state NMR techniques ( van Emmerik and van Ingen, 2019 ; Ackermann and Debelouchina, 2021 ; Shi et al, 2022 ). Indeed, these solid-state NMR studies have revealed that histone N-terminal tails retain considerable conformational flexibility even in the highly condensed chromatin environment ( Gao et al, 2013 ; Shi et al, 2018 ; Xiang et al, 2018 ; Shi et al, 2020a ; Zandian et al, 2021 ), which likely plays a significant role in recruitment of chromatin regulatory proteins, and enabled histone core dynamics ( Shi et al, 2020b ), base pairing in nucleosomal DNA ( Conroy et al, 2022 ), histone protein interactions with nucleosomal DNA ( Elathram et al, 2022 ) and with nucleosome binding peptides and proteins ( Xiang et al, 2018 ; le Paige et al, 2021 ), as well as the impact of PTMs on histone tail conformation and flexibility ( Shoaib et al, 2021 ) to be probed with atomic-resolution detail.…”
Section: Introductionmentioning
confidence: 99%